Local Context Influence, Activity Space, and Foodscape Exposure in Two Canadian Metropolitan Settings: Is Daily Mobility Exposure Associated with Overweight? - Alexandre Lebel; Yan Kestens; Robert Pampalon; Marius Thériault; Mark Daniel; S. V. Subramanian (Hindawi Limited, 2012)
It has become increasingly common to attribute part of the obesity epidemic to changes in the environment. Identification of a clear and obvious role for contextual risk factors has not yet been demonstrated. The objectives of this study were to explain differences in local overweight risk in two different urban settings and to explore sex-specific associations with estimated mobility patterns. Overweight was modeled within a multilevel framework using built environmental and socioeconomic contextual indicators and individual-level estimates of activity space exposure to fast-food restaurants (or exposure to visited places). Significant variations in local levels in overweight risk were observed. Physical and socioeconomic contexts explained more area-level differences in overweight among men than among women and among inhabitants of Montreal than among inhabitants of Quebec City. Estimated activity space exposure to fast-food outlets was significantly associated with overweight for men in Montreal. Local-level analyses are required to improve our understanding of contextual influences on obesity, including multiple influences in people's daily geographies.